Employment Contracts for the New World of Work. - Nel (Snr), Jan Kemp.; Nel (Jnr), Jan Kemp. (London : Knowledge Resources, 2021)
Employment Contracts for The New World of Work deals with the employment contract in South Africa and the importance of this document as the foundation of the commercial relationship between the employee and the employer. _x000D__x000D_It provides practical assistance and information to the entrepreneur, business owner, front-line manager, trade union representative and official, who is, no matter how experienced, always in need of a quick reference guide and source of knowledge._x000D__x000D_Content includes:_x000D__x000D_* Identifying the Parties to The Contract_x000D_* The Legislative Framework_x000D_* The Contract of Employment: Formation, Contents and Format_x000D_* Termination of Employment_x000D_* Pushing the Frontiers of Traditional Employment - Working from Home (WFH) And Hybrid Working_x000D_* Repudiation Breaches of Contract and Remedial Rights_x000D_* Disputes and Dispute Processes_x000D__x000D_Includes a FREE TOOLKIT with sample contracts, guidelines, policies, procedures and statutory regulations.
7.3 Examples of Repudiatory Conduct -- CHAPTER 8: DISPUTES AND DISPUTE PROCESSES -- 8.1 Introduction -- 8.2 Disputes Concerning Contracts of Employment -- 8.3 Unilateral Changes to Contract Terms and Conditions -- 8.4 Statutory Remedies for Unfair Dismissals -- 8.5 The Courts and Statutory Mechanisms -- 8.6 Private Arbitration -- CONCLUSION -- TOOLKIT: SAMPLE CONTRACTS, GUIDELINES, POLICIES, PROCEDURES AND STATUTORY REGULATIONS -- A. Sample Contracts and Guidelines -- 1. Basic Contract of Employment (Shopfloor/General Employees) -- 2. Letter of Appointment (Staff/Managerial) -- 3. Limited Duration/Temporary or Project-Based Contract of Employment -- 4. Domestic Worker's Contract of Employment (Department of Labour) -- 5. Agricultural/Farm Worker's Contract of Employment -- 6. Seasonal Employee's Contract of Employment -- 7. Independent Contractor's Agreement -- 8. Notes on Restraint of Trade and Confidentiality -- 9. Key-Performance Areas (KPAs) and Performance Agreement -- 10. Conventional Penalties Act and Sample Penalty, "Claw Back" Clause -- 11. Working from Home (WFH) Policy and Procedure -- 12. Electronic Communications Policy and Procedure/Internet Policy -- 13. Retirement Policy and Procedure -- 14. Remuneration and Incentive Scheme Guidelines -- 15. Maternity and Paternity Leave Policy and Procedure -- 16. Absenteeism Policy and Procedure -- 17. Poor Work Performance Policy and Procedure -- 18. Disciplinary Transgressions, Misconduct Code -- 19. Medical Incapacity Policy and Procedure -- 20. Alcohol and Drug Usage: Remedial Policy and Procedures -- 21. Health and Safety, and Medical Treatment Policy Guidelines -- B. Statutory Regulations -- 1. BCEA Statutory Minimum Conditions of Employment -- 2. Schedule 8 to The LRA - Code of Good Practice: Dismissal -- BIBLIOGRAPHY -- INDEX.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: South Africa; Labor contract; Electronic books